Propuesta de mejora en las líneas de casquillos y balas de 9mm en la planta de fabricación de la empresa Fame S.A.C. - Gamboa Soto, Wendy del Carmen (2018)
In the Industrial Sector for the National Security, currently, the manufacturing of munitions for Governmental Entities is awarded to a single company: FAME S.A.C. Consequently, the development of an efficient and effective production of this company affects directly the supply of munitions in the national market. In the production area of FAME S.A.C., a high number of stops were detected in the production line of 9 mm of cases and bullets. These stops were caused to a greater extent by defective tools, from the Tooling Plant. As the tools were indispensable pieces in most of machines, this thesis analyzes in detail the causes of stops due to defective tools and proposes solutions in order to minimize the number of stops in the production line of 9 mm of cases and bullets. The following steps to reduce the number of stops in the line of 9 mm of cases and bullets of this thesis will start by establishing the objectives and defining the project scope. The development of the thesis will include the implementation of the project, the time and the economic valuation using engineering tools and methodologies to get an appropriate solution to reduce the stops due to defective tools in the Manufacturing Plant of Cases and Bullets. Finally, it should be noted that the correctly application of the proposed solution implemented will have a high impact on the national production of munitions for national security.